The Management Innovation of Kuliah Kerja Praktek (KKP) - Saulina Panjaitan, Aropria; Rahardja, Untung; Aini, Qurotul; Lestari Santoso, Nuke Puji; apriliasari, dwi (APTISI Transactions on Management (ATM), 2022)
This study aims to provide innovation management for inputting practical work titles online based on Laravel. The rapid development of the positive number of Covid-19 has made the world restless, including the country of Indonesia, which has gone through more than 1 year of the pandemic period starting from March 2020 to May 2021. The surge in positive cases of Covid-19 has had a significant impact on the sustainability of the institution's teaching process. education. Covid-19 is forcing digital transformation towards the 4.0 education era. Technology is the only answer that can help during the pandemic, with technology the teaching and learning process continues, meetings, discussions and other things continue online. With digital transformation, conventional methods have been replaced, one of which is inputting the title ofPractical Job Training (KKP) at Raharja University which utilizes the ability of Ms. Excel. This offline KKP title input service must be replaced, given the existence of Large-scale Social Restrictions which require students to make long-distance contact with the KKP title inputting administrator and reduce the service for filling out forms which are quite time-consuming and the occurrence of data input errors. The method used in this research is the Agilemethod Scrum Tire which is a reference in working on Laravel-based technology. With the presence of this technology, it becomes a finding in replacing conventional methods and breakthroughs in the all-digital pandemic. The application of online KKP input can provide convenience and efficiency in the proces.